Health Information Needs of Public Library Leaders during COVID‐19. Issue 1 (14th October 2022) - Bossaller, Jenny; Kohlburn, Joe; Cho, Hyerim; Moulaison‐Sandy, Heather; Adkins, Denice
Abstract: During the COVID‐19 pandemic of 2020–2021, public library leaders across the United States were forced to make decisions quickly that affected the services and resources they were able to provide. However, the health information they had to make decisions on was imperfect and constantly changing. Interviews with 23 public library managers and directors revealed that more authoritative local data was needed for decision‐making and to share with their service populations. Overwhelmed public health system and/or suspicious or skeptical political environments hindered access to locally‐specific health information. Several respondents were uncomfortable creating information or making decisions without the guidance of health officials. Additionally, the library managers and directors described working as crisis managers, making decisions that impacted the health of their staff and their communities. In capturing and analyzing these "pandemic decision‐making stories, " this research informs future library information responses to community needs during times of crisis.